Epidemiological Situation on the Acute Intestinal Infections in the Jewish Autonomous Region in the Past Decade and After the Flood 2013 - T. V. Korita; V. A. Yanovich; G. G. Onishchenko; O. E. Trotsenko; E. S. Mironenko; P. V. Kopylov (Проблемы особо опасных инфекций, 2014)
Considerable aggravation of sanitary-hygienic situation forming the basis for occurrence of mass infectious disease outbreaks is observed when immense territories are water logged, and water supply systems are destructed. Therewith in order to provide control over the spread of acute enteric water-borne infections in the Jewish Autonomous Region investigated was the morbidity both in the last decade and after the flood period in 2013. The system of organizational and preventive actions included inspection of water intake constructions, zones of sanitary protection of water fences; laboratory control over the drinking water quality; organization of the homesteads patrolling for early detection of infectious diseases; monitoring of the infectious and parasitic diseases incidence rate; management of the vaccine prophylaxis; inspection of solid household waste storage sites and other epidemically significant objects in the flooded area; determination of necessary disinfectant quantity; provision of the population with information concerning implementation of the post-flood prophylactic measures. The actions undertaken permitted to get the epidemic situation on acute enteric infections including the water-dependent ones under control.